PENGARUH FUNGSI DALAM PENGUNAAN KONTEN IKLAN MEDIA SOSIAL TERHADAP BEHAVIOURAL INTENTION - Edy Yulianto Putra; Ilham syahputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study was conducted to determine whether the variables of service quality, social media sales promotion, trust, customer satisfaction on behavioral intentions at Japanese restaurants in Batam City. The independent variables in this study are service quality, social media sales promotion, trust, customer satisfaction and the dependent is behavioral intention. Researchers used SPSS version 26 software to analyze respondents' demographic data and then used SMARTPLS version 3.0 software to test and analyze the relationship between the variables. The results are based on hypothesis testing Service Quality, Social Media Sales Promotion, Trust has a significant positive effect on Customer Satisfaction and Behavioral Intentions. In addition, Customer Satisfaction also has a significant positive effect on Behavioral Intention. So it can be said that all positive significant. The results of this study, in increasing Behavioral Intention for Japanese restaurants in Batam, it is recommendedto Japanese restaurant business owners to be able to increase trust, service quality, social media sales promototion and customer satisfaction